Impact of a Heutagogical, Multimedia-Based Teaching Concept to Promote Self-Determined, Cooperative Student Learning in Clinical Radiology - Teichgräber, Ulf; Ingwersen, Maja; Mentzel, Hans-Joachim; Aschenbach, Rene; Neumann, Rotraud; Franiel, Tobias; Herzog, Aimée Barbara; Böttcher, Joachim; Pfeil, Alexander; Mensel, Birger; Kühnel, Christian; Freesmeyer, Martin; Fischer, Martin R.; Zottmann, Jan (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To date, didactic lecturing is a common method of university medical training. However, higher levels of competence to solve complex issues are hardly to be achieved with a largely passive learning style. We established and evaluated a heutagogical blended learning concept to investigate self-determined learning with a multimedia-based, interactive approach in the lecture room to teach clinical radiology.Materials and Methods In the 2019/2020 winter semester, we included 266 medical students in their fourth academic year in our prospective, observational study. Students participated in a series of 11 radiological lectures given by 10 lecturers. They were requested to prepare for lectures by watching learning videos. During the lecture, students had to answer key-feature questions (KFQ) in small groups and to jointly submit their answers by means of an audience response system (ARS). After each lecture and the exam, we conducted surveys and compared results with a historical control group. A focus group interview with lecturers was performed after conclusion of the lecture series.Results The students’ overall impression of the “flipped classroom” concept and their examination grades were superior to historical controls (overall impression: 1.5 [95 % CI 1.4–1.6] vs. 2.7 [95 % CI 2.5–2.9] rated on a scale from 1 to 6, p < 0.001; examination grades: 1.8 [95 % CI 1.7–1.9] vs. 2.0 [95 % CI 1.9–2.0] rated on a scale from 1 to 5, p < 0.001). Most students agreed that learning videos (76.6 %), ARS (88.5 %), KFQ (76.5 %), and solution-oriented small group discussions (83.7 %) were useful. Lecturers stated an improved convergence of demands on learning and clinical competence. However, they also emphasized an increased initial effort for implementation.Conclusion Students rated the overall benefit from the heutagogical “flipped classroom” concept as high. Examination grades improved. According to lecturers, the “flipped classroom” concept better matched later professional demands than traditional lectures.Key Points: Citation Format
Keywords: didactics; heutagogy; interactive learning environments; key feature questions; flipped classroom; medical education